Relative house price dynamics across euro area and US cities: convergence or divergence? - Paul Hiebert; Moreno Roma (European Central Bank (ECB), 2010)
This paper examines the time varying dispersion in city house price levels across the four biggest euro area countries compared with those in the United States. Using available city-level data over the period 1987-2008, it tests for price convergence and analyses key factors explaining price differentials in a panel regression framework including per capita income, population and relative distances. Results indicate limited evidence of convergence in city-level house prices despite synchronised cycles in the national aggregates for most countries since the 1990s. There is an important role for income differentials in explaining city-level house price dispersion in Germany, France, and the US (but not in Italy or Spain once unobserved city factors are taken into account). At the same time, population differences across cities play a role, though this appears to be associated with amenities specific to a particular location. In general, there has been a lower dispersion of city-level house prices in the four largest euro area economies compared with the US in conjunction with a lower estimated income elasticity for house price differentials. The results, particularly for income, appear to be robust to restricting the analysis to large urban centres.
Keywords: R21; R31; E31; 330; House price convergence; house price dispersion; house price drivers; panel data analysis; Immobilienpreis; Wohneigentum; Preisstreuung; Räumliche Verteilung; Großstadt; Deutschland; Frankreich; Italien; Spanien; USA